The spatio-temporal distribution of He (23S1) metastable atoms in a MHz-driven helium plasma jet is influenced by the oxygen/nitrogen ratio of the surrounding atmosphere. (2nd March 2015) - Winter, J; Sousa, J Santos; Sadeghi, N; Schmidt-Bleker, A; Reuter, S; Puech, V
Abstract: The density of helium He (2 3 S1 ) metastable atoms is measured in a 1.6 mm diameter MHz-driven atmospheric pressure helium plasma jet by laser absorption spectroscopy with spatial and temporal resolution. The surrounding atmosphere of the jet is varied from pure oxygen to pure nitrogen with a gas shielding device. The highest metastable density of 1.3 × 10 13  cm −3 is obtained in the center of the jet close to the nozzle exit at normal atmospheric air conditions. Within 0.3 mm in the radial direction and 2 mm in the axial direction, the He metastable density drops below the detection limit. The obtained He metastable lifetime is almost independent of the shielding gas composition. By analyzing the diffusion of shielding gas species into the effluent it is concluded that their density is too low to explain the observed He metastable lifetime. Instead, impurities from the feed gas, especially water molecules, are more likely to be responsible. However, a drastic change in metastable He density is observed when decreasing the amount of oxygen in the shielding gas. The lower the oxygen amount, the lower the metastable He density. For pure nitrogen, no He metastables are detected at all. By exchanging nitrogen with argon, a similar behavior is observed. Thus, it is concluded that it is the absence of ambient oxygen rather than the elevated presence of nitrogen, which is responsible for the observed decrease in the He (2 3 S1 ) density.